PENGGUNAAN KARYA CIPTA MUSIK DAN LAGU TANPA IZIN DAN AKIBAT HUKUMNYA - Hulman Panjaitan (Fakultas Hukum Universitas Kristen Indonesia, 2015)
Abstract Copyrightis avery important part of Intellectual Property Rights, especially inthe field of creative works of musicandsong;the infringement is very alarming and serious in Indonesia.Copyright is an exclusive right or special right which means that other people cannot take advantage of economic rights of creators on his creations without prior approval of the legal creators or copyright holders.The consequence is in each use of music for commercial businesses and or interests related to business activities/commercial purposessuch ascafes, hotels, restaurant sands of orthmust firstask approval from thecreators or copy right holders on the use of the music creation. Kata Kunci: Pengggunaan Karya Cipta Tanpa Izin